Análisis a los estados financieros a la empresa comercial Servicios Agrícolas la Siembra del Cantón Pindal. Periodos 2020-2021 - Montesdeoca Montesdeoca, Karina Anabel (2023)
The present curricular integration project titled "FINANCIAL ANALYSIS OF THE COMMERCIAL COMPANY AGRICULTURAL SERVICES 'LA SIEMBRA' IN PINDAL CANTON. PERIODS 2020-2021," was developed with the purpose to evaluate the economic and financial position of the company through the variations found in the vertical and horizontal analysis. Its objective is to understand the levels of liquidity, activity, indebtedness, and profitability by applying financial indicators. The development of both the theoretical and practical work is based on the application of different methods. The deductive and inductive methods were used to organize the collected information from general to specific. The analytical method was applied to analyze and interpret the financial statements for the periods 2020-2021. The synthetic method was used to define conclusions and recommendations that enable well-informed decision- making. The mathematical method involved performing operations, and the statistical method was used for data consolidation in tables and graphs. In order to achieve the first specific objective in the research work, the vertical and horizontal analyses were conducted to understand the real financial-economic situation of the company. Financial indicators of liquidity, activity, indebtedness, and profitability, specific to commercial activities were applied along with their respective interpretations and graphs, which are necessary to evaluate the financial, economic, and operational performance of the company. Additionally, in order to achieve the third objective, a financial analysis report is presented, which includes a synthesis of the obtained results, conclusions, and recommendations that serve as a guide for the manager-owner to make appropriate decisions that contribute to the improvement and continuity of the commercial enterprise. As the final objective, the cash budget is presented, enabling the anticipation and control of cash flows, establishment of short-term goals and objectives, and avoidance of cash shortage or excess problems.